Implementation of the Sustainable Development Goals Program in Oabikase Village, West Insana District, North Central Timor Regency - Naisoko, Liberius (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2024)
Implementation of the Sustainable Development Goals (SDGs) Program in Oabikase Village, West Insana District, North Central Timor Regency. Problem Formulation